Fotolibro “Huacas Urbanas” - Saurre Luna Victoria, David Alonso (2020)
Photography has gone through many artistic movements and different authors. One of these is the documentary photography that aspires to picture reality as it is, nonetheless, it' s full of different submovements. Having this in mind, taking values from the movement, Huacas Urbanas is born. Using techniques inspired from the work of Ansel Adams and Martín Chambi, this project pictures the huacas that are found inside of Lima to revalue them showing the beauty that is found inside of them and in their contrast with urban landscape.